2021
DOI: 10.1038/s41598-021-95635-x
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine does not compromise neuronal viability, synaptic connectivity, learning and memory in a rodent model

Abstract: Recent animal studies have drawn concerns regarding most commonly used anesthetics and their long-term cytotoxic effects, specifically on the nervous tissue. It is therefore imperative that the search continues for agents that are non-toxic at both the cellular and behavioural level. One such agent appears to be dexmedetomidine (DEX) which has not only been found to be less neurotoxic but has also been shown to protect neurons from cytotoxicity induced by other anesthetic agents. However, DEX’s effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…To assess whether a clinically relevant concentration of sevoflurane had any long-term effects on spatial learning, we used Morris water maze (MWM) as previously described [27,55]. Latency (time required to reach the hidden platform), distance swum, and the trajectory followed by the animals while swimming was monitored during each trial.…”
Section: Sevoflurane Exposure Resulted In Erratic Swimming Patterns B...mentioning
confidence: 99%
See 4 more Smart Citations
“…To assess whether a clinically relevant concentration of sevoflurane had any long-term effects on spatial learning, we used Morris water maze (MWM) as previously described [27,55]. Latency (time required to reach the hidden platform), distance swum, and the trajectory followed by the animals while swimming was monitored during each trial.…”
Section: Sevoflurane Exposure Resulted In Erratic Swimming Patterns B...mentioning
confidence: 99%
“…Dexmedetomidine has gained some notoriety in the past years as a possible neuroprotectant agent. Studies have looked at putative mechanisms underlying its neuroprotective effects at the molecular level and shown that dexmedetomidine may downregulate proteins implicated in apoptosis [13,25,51,89], promote neuronal outgrowth [12,55], modify mitochondrial morphology and function [52,55] and decrease inflammatory cytokines [53]. Behavioural studies where DEX was used as a pre-treatment prior to sevoflurane exposure have found improvements in swimming latency [24,90] and object recognition [23,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations